SCA13 causes dominantly inherited non-progressive myoclonus ataxia. (May 2017) - Montaut, Solveig; Apartis, Emmanuelle; Chanson, Jean-Baptiste; Ewenczyk, Claire; Renaud, Mathilde; Guissart, Claire; Muller, Jean; Legrand, André Pierre; Durr, Alexandra; Laugel, Vincent; Koenig, Michel; Tranchant, Christine; et al.
Abstract: Introduction: Spinocerebellar ataxia 13 (SCA13) is a rare autosomal dominant cerebellar ataxia. To our knowledge, its association to movement disorders has never been described. We aimed at reporting 8 new SCA13 cases with a focus on movement disorders especially myoclonus. Methods: We performed a detailed neurological examination and neurophysiological recording in 8 patients consecutively diagnosed with SCA13 between December 2013 and October 2015 and followed up in two French tertiary centers. Results: We identified mild subcortical myoclonus in all patients, with a homogenous clinical and electrophysiological pattern. Myoclonus ataxia was very slowly progressive, like the other symptoms of the disease, whatever the age of onset. Patients with R423H mutation had an earlier age of onset than patients with R420H mutation. Conclusions: Myoclonus appears to be frequent in SCA13. SCA13 should be considered facing non-progressive autosomal dominant myoclonus ataxia, and polymyographic recording should be included in the diagnosis work. Highlights: Myoclonus appears to be a very frequent feature of SCA13. The neurophysiological pattern of myoclonus is homogeneous. A subcortical generator is highly probable. Like the other signs of the disease, myoclonus appears to be very slowly progressive.